PENERAPAN METODOLOGI PENGEMBANGAN SISTEM WATERFALL PENGEMBANGAN APLIKASI BUKU TAMU BERBASIS ANDROID - Rizky Khairuna; Muhammad Dedi Irawan (Jurnal Ilmu Komputer dan Sistem Informasi, 2024)
Information systems are an important part of an agency because they can provide convenience in many ways, such as making data processing more effective, efficient in decision making, and can save time and costs. Guestbooks which are still done manually can cause confusion in recapitulating the desired guest data and can take quite a long time. Currently at the Sei Kera Hulu Subdistrict Office, processing of guest data is still done manually using stationery. With this, the researcher developed Android-based media which aims to record guest data and facilitate access to guest needs and improve the guest experience in order to improve operational efficiency, data accuracy and the overall guest service experience. The research process carried out starts from problem formulation, determining objectives, literature study, data collection, analysis of current and required systems, system interface design, implementation and testing. The system development method used in this research is the waterfall method which consists of five stages. The results of this research are that the system can run well, making it easier to access guest needs, increasing operational efficiency, data accuracy and the overall guest service experience.